PENENTUAN WAKTU PENGAMBILAN BENIH DAN DIET IKAN SIDAT (Anguilla bicolor Mc Clelland) DI SUNGAI SERAYU - Setijanto Setijanto; Isdy Sulistyo; Eko Budianto (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2014)
The purpose of this study is to know when appropriate time to catch the fish and to observe dietary fish eel (Anguilla bicolor Mc Clelland) found at River Serayu. The information obtained is important for the cultivation of this species. Sampling is carried out at two stations upstream section (Bendung Gerak Serayu) employing method traps and downstream (river estuary) with opyok method. Replication is done 2 times a month for 1 year. The results showed that the elvers, juvenile and adults tend to get caught throughout the year and with a peak in July. Based on the study, the capture of eels in the River Serayu can be done throughout the year. Diet examination reveals that Polychaeta, benthic insects, Malacostraca, Pisces, and gastropods are food of eels. Polychaeta and benthic insects are the main food for eels with size of <30 cm, while the Malacostraca and gastropods are the main food for eels with size of > 30 cmKeywords : eels, River Serayu, diet, A bicolor